Konseling Individu dalam Meningkatkan Motivasi Belajar pada Masa Pandemi di SMA Muhammadiyah 4 Yogyakarta (Altruism: The Indonesian Journal of Community Engagement, 2024)
The purpose of this individual counseling activity was motivated by the presence of students who had less enthusiasm for learning during this pandemic on the grounds that many of their duties, the material did not understand because students were required to read to understand the learning material sent by the teacher themselves. The implementation of individual counseling is carried out by meeting the counselor with a client individually and the counselor tries to develop the client's personality and provides assistance and helps the client solve the problem he is facing in accordance with the stages of individual counseling, which is carried out in 3 stages, namely the initial stage, the core stage and the final stage. Tujuan dari kegiatan konseling individual ini dilatarbelakangi oleh adanya siswa yang kurang semangat belajar pada masa pandemi ini dengan alasan banyak tugasnya, materinya kurang dipahami karena siswa diharuskan membaca untuk memahami materi pembelajaran yang dikirimkan oleh guru itu sendiri. Pelaksanaan konseling individual dilakukan dengan cara mempertemukan konselor dengan klien secara individu dan konselor berusaha mengembangkan kepribadian klien serta memberikan bantuan dan membantu klien memecahkan masalah yang dihadapinya sesuai dengan tahapan konseling individu yang dilakukan. keluar dalam 3 tahap yaitu tahap awal, tahap inti dan tahap akhir.